PENGEMBANGAN MEDIA PEMBELAJARAN SMART JENGA BERBASIS KEARIFAN LOKAL MUATAN IPS KELAS V SD - Taofik; Nidya Chandra Muji Utami; Indah Wardatussa’idah; Anggit Aruwiyantoko; Indah Maulida Savon; Laila Aska Fuadiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to produce learning media in the form of smart jenga for social studies content for grade V elementary school. This type of research is research and development with ADDIE development design consisting of 5 stages, namely: analyze, design, develop, implement, and evaluate. Smart jenga consists of wooden blocks, question cards, point cards and guidebooks. The results of research and development are categorized as feasible according to material experts with a score of 90, media experts with a score of 98.5 and language experts with a score of 98. The results of user trials involving 21 respondents with an average score of 81.15. The final conclusion of this study is that smart jenga media is feasible to be used in learning.